Association of sociodemographic and lifestyle factors with dietary patterns among men and women living in Mexico City: A cross-sectional study - Oviedo-Solís, Cecilia Isabel; Hernández-Alcaraz, César; Sánchez-Ortíz, Néstor Alonso; López-Olmedo, Nancy; Jáuregui, Alejandra; Barquera, Simón (Frontiers in Public Health, 2022)
Background Diet is one of the leading risk factors for non-communicable diseases and is related to sociodemographic and lifestyle factors, including sex. These associations vary across populations. We aimed to investigate which factors are associated with dietary patterns among adults living in Mexico City by sex. Methods We used data from the Mexico City Diabetes Representative Study, a cross-sectional, multistage, stratified, and cluster-sampled survey in Mexico City (n = 1,142; 413 men and 729 women). Dietary information was collected using a semi-quantitative food frequency questionnaire. Foods and beverages were categorized into 23 food groups to identify dietary patterns by cluster analysis. Sociodemographic and lifestyle variables included were self-reported through standardized questionnaires. We assessed the association of sociodemographic and lifestyle factors with dietary patterns through a multinomial logistic model stratified by sex. Results We identified three dietary patterns: basic, prudent, and fast food. Among men and women, higher school attainment was associated with a lower relative probability of having a basic rather than prudent dietary pattern (women: RRR = 0.8, 95% CI: 0.8, 0.9; men: RRR = 0.8, 95% CI: 0.7, 0.9). Divorced or separated men (RRR = 3.8, 95% CI: 1.3, 11.2) and those living with a partner (RRR = 2.6, 95% CI: 1.1, 6.1) had a higher relative probability of consuming a fast food dietary pattern than the prudent one, compared to single men. Men living with a partner (RRR = 3.0, 95% CI: 1.1, 8.6) or working long shifts (RRR = 3.8, 95% CI: 1.3, 11.1) had a higher probability of consuming a basic pattern rather than a prudent one compared to peers. Among women, those with high SES had a lower probability of consuming the “basic” pattern rather than the “prudent” pattern compared to those with low SES. No lifestyle factors were associated to dietary patterns. Conclusions Men living in Mexico City with lower education, age, non-single, and working long hours (i.e., more than the established by the law), and women with lower age, education, and socioeconomic level are prone to adhere to unhealthy diets. These associations are likely to be driven by gender roles.